Surgical treatment of congenital heart malformation with left-to-right shunt coexists with pulmonary hypertension - Mozol, Krzysztof; Kwaśniak, Ewelina; Haponiuk, Ireneusz; Szafranek, Adam; Maruszewski, Bohdan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Pulmonary hypertension is a significant risk factor of mortality and morbidity in congenital heart malformations with left-to-right shunt. The increased pulmonary blood flow lead to permanent endothelial cells stimulation, consequently to their dysfunction, increased pulmonary vascular resistance, acute or progressive right ventricle failure. The early surgical correction prevent up mention pathological tract. The optimal time of surgery is still leading therapeutic problem. The specific and non-specific treatment of pulmonary vascular resistance would improve surgical results. Extracorporeal membrane oxygenation (ECMO) or lung or heart – lung transplantation are option for patients with contraindications for surgical treatment and/or resistance for up mention treatment.